Network meta-analysis comparing WALANT, locoregional, local and general anesthesia techniques in carpal tunnel release - Laurentiu-Cosmin Focsa; Pierre-Alban Bouché; Thomas Apard; Daphné Querel; Marc-Antoine Rousseau; Jules Descamps (EFORT Open Reviews)
Purpose: To compare anesthesia techniques (WALANT (wide-awake anesthesia no tourniquet), locoregional anesthesia, local anesthesia with tourniquet or sedation) for carpal tunnel release (CTR). Methods: A comprehensive literature search was conducted on PubMed, MEDLINE, Embase and the Cochrane Library up to May 2023. Two independent reviewers selected the studies and extracted the data. The primary outcomes included the pain experienced at the moment of anesthesia and during the surgery and the mean morphine equivalents (MME) administered following the surgery and overall patient satisfaction. Our secondary outcomes consisted of the mean room occupancy time and the mean duration of the procedure, followed by the complication rate. The review process was conducted according to PRISMA guidelines. Results: A total of 3166 studies were identified, which included 23 studies comparing various anesthesia types and 28,748 CTR surgeries. The WALANT group experienced significantly lower pain levels during anesthesia (−2.67 (95% CIs: 0.12–4.99)) and surgery (−2.04 (95% CIs: 0.08–4.07)) compared to the local anesthesia group. There was no difference in the use of MME for pain relief among different anesthesia techniques. Satisfaction rates were comparable, but WALANT exhibited the highest probability for utmost satisfaction. The mean room occupancy time was lower in patients receiving local anesthesia compared with when sedation was added, with a mean difference of −27.16 (95% CIs: −52.03 to −1.85). Conclusions: The WALANT technique for CTR reported better outcomes for pain (during anesthesia and surgery), higher satisfaction and low probability to expand the operating room occupancy time. Level of evidence: Level II of evidence.